Establishment of Neurospora crassa as a model organism for fungal virology - Honda, Shinji; Eusebio-Cope, Ana; Miyashita, Shuhei; Yokoyama, Ayumi; Aulia, Annisa; Shahi, Sabitree; Kondo, Hideki; Suzuki, Nobuhiro (Nature communications, 2020)
The filamentous fungus Neurospora crassa is used as a model organism for genetics, developmental biology and molecular biology. Remarkably, it is not known to host or to be susceptible to infection with any viruses. Here, we identify diverse RNA viruses in N. crassa and other Neurospora species, and show that N. crassa supports the replication of these viruses as well as some viruses from other fungi. Several encapsidated double-stranded RNA viruses and capsid-less positive-sense single-stranded RNA viruses can be experimentally introduced into N. crassa protoplasts or spheroplasts. This allowed us to examine viral replication and RNAi-mediated antiviral responses in this organism. We show that viral infection upregulates the transcription of RNAi components, and that Dicer proteins (DCL-1, DCL-2) and an Argonaute (QDE-2) participate in suppression of viral replication. Our study thus establishes N. crassa as a model system for the study of host-virus interactions. The fungus Neurospora crassa is a model organism for the study of various biological processes, but it is not known to be infected by any viruses. Here, Honda et al. identify RNA viruses that infect N. crassa and examine viral replication and RNAi-mediated antiviral responses, thus establishing this fungus as a model for the study of host-virus interactions.